Semantic Analysis of Toshihiko Izutsu in the Phrase 'Al-'Urwatul Wutsqo - Fadhilah, Umi; Nugroho, Kharis (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2023)
One of the phrases found in the Qur'an is "al-'urwatul wutsqo," mentioned in two different verses, namely Qur'an Surah Al-Baqarah verse 256 and Surah Luqman verse 22. In order to delve deeper into the meaning of this phrase, the author will apply the semantic analysis of the Qur'an developed by Toshihiko Izutsu. According to Izutsu, the semantics of the Qur'an is an attempt to reveal the worldview (weltanschauung) embedded in the Qur'an through the analysis of the meanings of the vocabulary or key terminology contained within it. This research approach involves exploring the basic meanings and relational relationships of the phrase "al-'urwatul wutsqo" using both syntagmatic and paradigmatic analysis, as well as research on the historical development of its meaning synchronically and diachronically.